A Case Study of Academic Vocabulary in a Novice Student’s Writing at a UK University - Dana Therova (Yayasan Visi Intan Permata, 2021)
Mastering appropriate writing style is one of the challenges frequently experienced by novice student writers entering higher education. Developing academic writing skills is, however, crucial for students new to academic settings since written assignments constitute the main form of assessment in tertiary education. Novice student writers thus need to acquire the writing conventions used in academic settings to achieve success in high-stakes assessment. Underlying success in academic writing is the usage of academic vocabulary regarded as a key feature of academic writing style. Through textual analysis accompanied by interview data utilising the ‘talk around text’ technique, this corpus-based case study reports on the deployment of academic vocabulary in four genres of assessed academic writing produced by one international foundation-level student at a UK university. The findings reveal a small number of newly acquired academic vocabulary items deployed in each written assignment with all new academic words having been acquired from reading materials. In addition, the important role that the topic and genre play in student written production becomes apparent. These findings have potentially important pedagogical implication for contexts catering for novice student writers entering tertiary education, such as foundation programmes or pre-sessional courses.